Extreme Low‐Latitude Total Electron Content Enhancement and Global Positioning System Scintillation at Dawn. Issue 9 (1st September 2021) - Mrak, Sebastijan; Semeter, Joshua; Nishimura, Yukitoshi; Coster, Anthea J.
Abstract: We report on an extreme ionospheric plasma density enhancement and Global Positioning System (GPS) scintillation at dawn, observed within the expanding equatorial ionization anomaly (EIA). The total electron content (TEC) in central America reached 50 TECu at sunrise, the value almost twice as high as the normal afternoon peak. The enhanced EIA expanded poleward and westward from just below 20° magnetic latitude (MLAT) to beyond 30° MLAT at sunrise. The chief ramification of the enhanced EIA was strong GPS scintillation which was observed poleward of 30° northern MLAT and lasted until 8:00 local time. In total, the amplitude scintillation and phase fluctuations lasted for ∼5 h at latitudes north of 20°MLAT in central America. Plain Language Summary: Low latitude ionosphere is conducive to a Rayleigh‐Taylor instability inherent to the region where magnetic field lines are parallel to the Earth. The instability's growth rate typically peaks just after sunset, whereby an enhanced eastward electric field at the terminator facilitates its growth. The instability promotes profound density depletions that rise into higher altitudes, where small‐scale irregularities develop. The resulting density irregularities are the most profound space weather threat to traversing radio signals. The timing observed scintillations follow the development of the instability, thereby the post‐sunset local times are the most susceptible to radio scintillations. We present observations where this instability developed in the early morning, and rapidly expanded at the sunrise instead. The instabilities caused severe scintillations of Global Positioning System signals, reaching latitudes of Yucatan, Mexico. Key Points: Observations show expansion of equatorial ionization anomaly (EIA) beyond 35° magnetic latitude at a pre‐dawn time Total electron content of the EIA's northern crest in central America exceeded 50 TECu at sunrise The EIA was accompanied by equatorial plasma bubbles, causing severe Global Positioning System scintillations lasting for 5 h around sunrise